Studies on Mycoflora and Mycotoxin Infestationin Shorea robusta Gaertn. f - Singh, Punam Kumari; Shukla, A. N. (Indian Forester, 2005)
Studies were carried out om fungal infestation and mycotoxin contamination in fresh and stored seed samples of Shorea robusta. In fresh samples 5 fungi namely Aspergillus flavus, Alternaria alternata, Cladosporium cladosporioides, Fusarium sp. and Rhizopus sp. Were recorded, whereas in stored samples 9 fungi namely A. flavus, A. alternata, A. niger, C. cladosporioides, Cylindrocladium sp. Phoma sp., Fusarium sp., Penicillium citrinum. and Rhizopus sp. were found associated. The pattern of mycoflora incidence was significantly different in samples from all three sources. Interaction of source and season was significant for all fungi observed in S. robusta. The mycotoxin producing fungi were screened for their toxin producing abilities. The amount of aflatoxin produced by toxigenic isolates was quite high. Aflatoxins were detected in almost all samples analysed for mycotoxin contamination.